Flavonoids from the Genus Euphorbia: Isolation, Structure, Pharmacological Activities and Structure-Activity Relationships - Douglas Kemboi Magozwi; Mmabatho Dinala; Nthabiseng Mokwana; Xavier Siwe-Noundou; Rui W. M. Krause; Molahlehi Sonopo; Lyndy J. McGaw; Wilma A. Augustyn; Vuyelwa Jacqueline Tembu (MDPI AG, 2021)
Plants of the genus Euphorbia are widely distributed across temperate, tropical and subtropical regions of South America, Asia and Africa with established Ayurvedic, Chinese and Malay ethnomedical records. The present review reports the isolation, occurrence, phytochemistry, biological properties, therapeutic potential and structure-activity relationship of Euphorbia flavonoids for the period covering 2000-2020, while identifying potential areas for future studies aimed at development of new therapeutic agents from these plants. The findings suggest that the extracts and isolated flavonoids possess anticancer, antiproliferative, antimalarial, antibacterial, anti-venom, anti-inflammatory, anti-hepatitis and antioxidant properties and have different mechanisms of action against cancer cells. Of the investigated species, over 80 different types of flavonoids have been isolated to date. Most of the isolated flavonoids were flavonols and comprised simple O-substitution patterns, C-methylation and prenylation. Others had a glycoside, glycosidic linkages and a carbohydrate attached at either C-3 or C-7, and were designated as d-glucose, l-rhamnose or glucorhamnose. The structure-activity relationship studies showed that methylation of the hydroxyl groups on C-3 or C-7 reduces the activities while glycosylation loses the activity and that the parent skeletal structure is essential in retaining the activity. These constituents can therefore offer potential alternative scaffolds towards development of new Euphorbia-based therapeutic agents.